Large cell neuroendocrine tumor of lung with hemorrhagic cerebral metastasis: A case report - Aalok Kumar Yadav, MD; Amrit Bhusal, MBBS; Tek Nath Yogi, MBBS; Santoshi Yadav, MBBS; Bhupendra Prasad Yadav, MD Pathology (Radiology Case Reports)
Large cell neuroendocrine carcinoma (LCNEC) of the lung is a rare, high-grade malignancy within the spectrum of pulmonary neuroendocrine tumors, characterized by aggressive behavior and poor prognosis. LCNEC commonly metastasizes to the liver, bone, and adrenal glands, with brain metastasis occurring in 10-20% of cases. Hemorrhagic cerebral metastasis, however, is infrequent and its pathophysiology remains poorly understood. Advanced imaging, including CT and MRI, plays a critical role in identifying both primary tumors and atypical metastatic patterns, such as hemorrhage, which complicates diagnosis and treatment planning. The presence of hemorrhagic brain metastases suggests tumor-induced vascular disruption, but the underlying mechanisms are not fully elucidated. We report a case of a-56-year-old female presented with progressive cough, hemoptysis, and weight loss, was diagnosed with LCNEC. Imaging revealed a left upper lobe mass with central necrosis, bronchial involvement, and lymph node enlargement. Contrast-enhanced brain MRI identified multiple cerebral metastases, one of which demonstrated hemorrhagic transformation, a rare complication in LCNEC, which was confirmed by histological examination by staining positive for neuroendocrine markers like chromogranin A and synaptophysin. This case highlights the importance of early diagnosis and advanced imaging in the management of LCNEC, especially in cases with CNS involvement. However, further research into the molecular and vascular mechanisms of hemorrhagic transformation in LCNEC could inform therapeutic strategies for patients with advanced disease.